Aktualisasi Pembelajaran PAI di Masa Pandemi Covid-19 Ditinjau dari Teori Pembelajaran E-Learning di SMK PGRI - Wulandari, Hilma Dian; Badrus, Badrus (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Online learning is a challenge for Islamic religious educators to convey their learning materials to be accepted and practiced by students. The focus of research in this study is, (1) How is PAI Learning in the Pandemic Period at SMK PGRI 2? (2) What is the Impact of PAI Learning in the Pandemic Period at SMK PGRI 2? (3) How is the Actualization of PAI Learning in the Pandemic Period in terms of E-Learning Learning Theory at SMK PGRI 2? This research is qualitative research with the type of case study research. The results showed: (1) PAI learning in SMK during the Pandemic used online learning methods, and the media used were Google Classroom, Moodle, and Google Meet. (2) The impact is that teachers must learn about technology and learning media. In the implementation of learning, students are bored and not enthusiastic, and signals and quotas are limited, and evaluation is only cognitive. 3) The e-learning developed in this SMK uses Moodle and Google Classroom. It means that e-learning is one of the supporting learning tools and an effective media for the learning process during the Pandemic.